Training on Making Crispy Chicken to Improve the Economy of Housewives - Talebe, Yusnaini B; Uriya, Sri Wahyuni; Lestari, Sri; Nasim, Abu Sahman (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Crispy fried chicken is a popular fast food item in Indonesia, and it can be made even more appealing by combining spicy flavours with cheese. This modern twist on a classic dish makes it enjoyable for all ages, especially young people. Many housewives in Bobaneigo Madihutu Village who are currently unemployed or underemployed lack a stable income. To address this, we are offering training in crispy chicken preparation to improve the economic opportunities for these women. The training session was held at Campus IV of Khairun University in Bobaneigo Village, Madihutu District, West Halmahera, North Maluku. It was attended by 20 local housewives and Agricultural Faculty students involved in community service activities. Pre- and post-training tests indicated a significant increase in the participants' knowledge about making crispy fried chicken. The feedback from the attendees was highly positive, highlighting the usefulness of the training and the new insights gained into chicken preparation. Overall, the training was well-received and met its objectives effectively